Kebijakan Dumping sebagai Perdagangan Ber-ketidakadilan dalam Perspektif Siyasah Al-Ighraq - Regita Cahyani Muis, Afni; Arleta, Abrilian Putri; Talo, Angelia Islamiati (Pusat Pendidikan dan Pelatihan Aparatur Perdagangan, 2023)
This study aimed to analyze the extent of dumping practices on Indonesian textile exports to Turkey which reviewed with siyasah al-ighraq. The imposition of anti-dumping by Turkey was due to an accusation response of dumping by Indonesia. Whereas as a ratifying country of the World Trade Organization (WTO), Turkey has the authority to investigate imported products into its country and also has the right to impose import duties, especially tax rates if the imported products have been accompanied by the importing country. With the siyasah al ighraq approach, the application of a lower price than the market price, it can be determined the extent of Indonesia's legal status in the imposition of anti-dumping. Finally, by using a qualitative method that presented in a sequential explanatory approach, foremost in Islamic perspective. That is siyasah al-ighraq with import duties in terms of the General Agreement on Trade and Tarrifs (GATT) or WTO penalties. The result is the policiy is required to act in protecting the rights of his people, including dealing with dumping practices